Design and Evaluation of a Pressure-Based Typing Biometric Authentication System. (23rd June 2008) - Eltahir Eltahir, Wasil Elsadig Wasil Elsadig; Salami Salami, M. J. E. M. J. E.; Ismail Ismail, Ahmad Faris Ahmad Faris; Lai Lai, Weng Kin Weng Kin
Abstract : The design and preliminary evaluation of a pressure sensor-based typing biometrics authentication system (PBAS) is discussed in this paper. This involves the integration of pressure sensors, signal processing circuit, and data acquisition devices to generate waveforms, which when concatenated, produce a pattern for the typed password. The system generates two templates for typed passwords. First template is for the force applied on each password key pressed. The second template is for latency of the password keys. These templates are analyzed using two classifiers. Autoregressive (AR) classifier is used to authenticate the pressure template. Latency classifier is used to authenticate the latency template. Authentication is complete by matching the results of these classifiers concurrently. The proposed system has been implemented by constructing users' database patterns which are later matched to the biometric patterns entered by each user, thereby enabling the system to accept or reject the user. Experiments have been conducted to test the performance of the overall PBAS system and results obtained showed that this proposed system is reliable with many potential applications for computer security.